The Impact of Obstetrician/Gynecologist Hospitalists on Maternal Quality of Care in Yogyakarta Indonsia: A Cohort Study - Eugenius Phyowai Ganap; Mohammad Hakimi; Soerjo Hadijono; Ova Emilia (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: The hospitalist is defined by 24-hour a day/7 day a week physician who assists or is employed by the hospital to manage patients, triage and emergencies. The hospitalist model in obstetric care that was introduced over the last decades now has an important role in care delivery management with the potential positive impact on maternal outcomes. Unfortunately, in Indonesia there were limited data available related to the implementation of hospitalist model and the impact on maternal quality of care.Objective: To determine the impact of obstetrician/gynecologist hospitalist on maternal quality care. Method: This research design was a retrospective cohort. Participants included were the patients in the time before and after implementation of obstetrician/gynecologist hospitalist policy during October 2013 until September 2014. Univariate and multivariate analysis were conducted to evaluate and determine the factors, which significantly contribute to maternal outcomes.Result and Discussion: We included a total of 71 patients (30 in the on-call group and 41 in the full time hospitalist group). Univariate analysis indicated mean response time was significantly different in the hospitalist group compared to the on-call group (65.3 ± 25.89 vs 84 ± 22.29 mins; p = 0.002). Implementation of full-time hospitalists did not impact the ICU admission and transfusion incidence.Conclusions: Implementation of the full-time hospitalist model was associated with a significant improvement of response time in emergency obstetric care without affecting maternal outcomes.Keywords: Maternal mortality, obstetrician/gynecologist hospitalist, labor and delivery, maternal care, ICU response time